AN AUDITING QUALITY DETERMINANTS AND THEIR IMPACT ON IRAQI COMMERCIAL BANKS FINANCIAL PERFORMANCE-AN APPLIED STUDY ON A SAMPLE OF NINE BANKS FROM 2012- 2018 - Ahmed Mushrif Rashid; Sinan R. Jasim; Ahmed Fadhil Saleh (Scholar Express Journals, 2025)
The study aimed to clarify the effect of the existing relationship between auditing quality determinants, which were represented in the bank's size subject to auditing, wages, size and age of the audit offices, and financial performance indicators such as return on stocks, ownership percentage and trading ratio. The study sample has taken (9) Iraqi banks operating in the Iraq Stock Exchange for the period from 2012 to 2018, With a total of (63) questionnaire, which were sufficient to apply the method of panel data, and through the comparison in the analysis process between each of the aggregate regression model and the fixed or random effects model. The comparison between these models was based on the Haussmann test to determine the best model in the analysis process. The most important results of the study nevertheless were a direct relationship to the variable of bank size subject to auditing and the financial performance indicators, the inverse relationship of the variable of audit services fees with financial indicators, and the absence of any significant impact for each of the size & age of the audit offices. The study recommended the necessity of having officially disclosed financial reports for the audit services offices in the Iraqi business environment. plus, the need of legal and legislative system that obliges the audit services offices to be adhere with.
Keywords: Auditing quality determinant; Financial performance indicators; Panel data